Mind the gap: analysis of two pilot projects of a home telehealth service for persons with complex conditions in a Swedish hospital - Carla Sacchi; Karolina Andersson; Marta Roczniewska; Jamie Linnéa Luckhaus; Moa Malmqvist; Lars Peter Rodmalm; Karin Lodin; Rebecca Mosson; Petra Danapfel; Carolina Wannheden; Pamela Mazzocato (BMC, 2023)
Abstract Background Developing and implementing home telehealth (HTH) services for patients with chronic conditions is a challenge. HTH services provide continuous and integrated care to patients, but very often pilot projects face non-adoption and abandonment issues. Change processes in healthcare are often complex and require learning to adapt to non-linear and unpredictable events. Complexity science can thus provide a complementary view to the predominant Quality Improvement (QI) approach in healthcare. In this study of two pilot projects in a Swedish hospital, we explore how a theory-driven approach can be used (a) to support the development of a self-monitoring HTH service in hospital care and (b) to evaluate staff and patients' experiences from early adoption. Methods To plan and evaluate the service for the recipients (i.e., patients and healthcare providers), we used the Plan-Do-Study-Act (PDSA) tool in combination with two complexity-informed frameworks: the Non-adoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) framework, and the joint Complexity Assessment Tool (CAT). The theory-informed development process led to two pilot projects of an HTH service for patients with heart failure and COVID-19. We collected data from multiple sources (project documents, a survey on readiness for change among staff, and semi-structured interviews with patients and staff) and analyzed the data using descriptive statistics and qualitative content analysis with a deductive approach. Results Patients and staff perceived the services as valuable as they enabled rapid feedback, and improved communication and collaboration between patients and healthcare providers. Yet, despite the extensive development efforts, there was a perceived gap between how individuals valued the service and the capacity of adopters, the organization, and the wider system to effectively integrate these services into routine care. Conclusions The combined use of PDSA, NASSS, and CAT can support the development and evaluation of HTH services that are perceived as valuable by individual patients and staff. For successful adoption, the value for individuals must be supported by organizational efforts to learn how to integrate new routines and tasks into clinical practice and daily life, and how to coordinate multiple providers within and outside the hospital walls.